2018
DOI: 10.1093/ofid/ofy001
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir-Based Direct-Acting Antiviral Therapies for HCV in People Receiving Opioid Substitution Therapy: An Analysis of Phase 3 Studies

Abstract: BackgroundHepatitis C virus (HCV) direct-acting antiviral therapy is effective among people receiving opioid substitution therapy (OST), but studies are limited by small numbers of nongenotype 1 (GT1) patients. The aim of this study was to evaluate the treatment completion, adherence, SVR12, and safety of sofosbuvir-based therapies in HCV patients receiving and not receiving OST.MethodsTen phase 3 studies of sofosbuvir-based regimens included ION (ledipasvir/sofosbuvir ± ribavirin for 8, 12, or 24 weeks in GT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
1
32
1
Order By: Relevance
“…In studies that did not provide adherence support, adherence was assessed by pill count (n = 3), a participant‐completed electronic medication diary (n = 1) or an electronic blister back (n = 1) . Fifteen studies reported treatment discontinuation: in recent PWID (n = 5) or OST recipients (n = 10) . Reasons for discontinuation included death, incarceration and loss to follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies that did not provide adherence support, adherence was assessed by pill count (n = 3), a participant‐completed electronic medication diary (n = 1) or an electronic blister back (n = 1) . Fifteen studies reported treatment discontinuation: in recent PWID (n = 5) or OST recipients (n = 10) . Reasons for discontinuation included death, incarceration and loss to follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…In total 16 studies, were deemed to be of high quality (NOS ≥ 7 or modified NOS ≥ 5). In studies with comparison groups, the most common source of potential bias was a possible difference between the recent PWID or OST group and the comparison group in terms of cirrhosis or other baseline factors such as age or genotype . This was either because of lack of reporting of baseline characteristics by recent PWID or OST group, or reporting of a statistically significant difference between groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, OST and active drug use should not be regarded as exclusion for treatment . DAA treatment in OST patients and PWID, show that SVR rates of >95% can be reached . Furthermore, low reinfection rates of 2‐6 per 100 person‐years (PY) have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have now clearly demonstrated that neither mental health concerns nor substance use greatly affect treatment outcomes. Multiple studies have shown high treatment completion and SVR rates among individuals receiving opiate agonist therapy (26,27). More recently, a multicentre study enrolled 103 participants who were actively injecting, of whom 100 completed therapy with 94% SVR (28).…”
Section: Treat Where Identified: Cure Among Current or Former People mentioning
confidence: 99%